Preliminar study on BDNF regulation by DNA methylation in Mesial Temporal Lobe Epilepsy - Ferreira, R. (2019)
Background and aims: Brain-derived neurotrophic factor (BDNF) is a neurothrophin associated with a wide range of neurophysiological processes, such as neurogenesis, gliogenesis, synaptogenesis and neuroprotection. BDNF has been described as overexpressed in hippocampus of both animal models and Mesial Temporal Lobe Epilepsy (MTLE) patients. Gene expression may be modulated by DNA methylation of the respective promoter regions. We sought to analyze, the DNA methylation of the BDNF exon I promoter, a region associated with neuronal imbalance